Study and characterization of corrosion in welds of modified 316L stainless steel for Urea Service - Fernández de Romero, Matilde; Troconis de Rincón, Oladis (Rev. Téc. Fac. Ing. Univ. Zulia)
This paper presents the results on the corrosion study, in welded zones of modified 316L Stainless Steel for Urea service. The tests involve chemical and structural features of base metal, N.D.E with dye check and x-ray analysis of parent metal and weld bead using SEM and TEM Techniques and corrosion Huey test. The tests performed verified the original specification of material with some non-metalic inclusions present (NiS). Crome rich phases that act as depleting agents were not detected, this reinforces the fact that corrosion failure can not be attributed to foreing phases. The results of the analysis lead to the conclusion that failure occurs due to the corrosive effect of ammonia carbamate on high residual stresses with lack of passivation. Crevice Corrosion was detected.